Atomic photoionization experiment by harmonic-generation spectroscopy - Frolov, M. V.; Sarantseva, T. S.; Manakov, N. L.; Fulfer, K. D.; Wilson, B. P.; Tross, J.; Ren, X.; Poliakoff, E. D.; Silaev, A. A.; Vvedenskii, N. V.; Starace, A. F.; Trallero-Herrero, Carlos A. (My University, 2016)
Measurements of the high-order-harmonic generation yield of the argon (Ar) atom driven by a strong elliptically polarized laser field are shown to completely determine the field-free differential photoionization cross section of Ar, i.e., the energy dependence of both the angle-integrated photoionization cross section and the angular distribution asymmetry parameter.
Citation: Frolov, M. V., Sarantseva, T. S., Manakov, N. L., Fulfer, K. D., Wilson, B. P., Tross, J., . . . Trallero-Herrero, C. A. (2016). Atomic photoionization experiment by harmonic-generation spectroscopy. Physical Review A, 93(3), 5. doi:10.1103/PhysRevA.93.031403
Keywords: Angular-Distribution; Photoelectrons; Dynamics; Distributions; Ionization; Field